Drivers of compositional turnover of narrow-ranged versus widespread naturalised woody plants in South Africa - de Beer, Isabella W.; Hui, Cang; Botella, Christophe; Richardson, David M. (Frontiers in Ecology and Evolution, 2023)
Alien trees and shrubs have become increasingly common invaders globally and have caused major negative impacts to ecosystems and society. Non-native woody plant species make up the majority of legislated invasive alien taxa in South Africa and contribute substantially to recorded impacts. It is of management interest to elucidate the macroecological processes which govern the assembly of alien taxa, as this is expected to be associated with anthropogenic factors (human activity, introduction events, pathways of propagule dispersal mediated by humans) and bioclimatic factors (diurnal temperature range and precipitation gradients). These analyses require large species-occurrence datasets with comprehensive sampling across broad environmental conditions. Efforts of citizen scientists produce large numbers of occurrence records in a consistent manner which may be utilized for scientific investigations. Although these data sources contain substantial sampling bias, such bias can be mitigated using statistical modelling of background points estimated from a Target Group (TG) of species which identifies well sampled communities. The drivers of assembly for alien plants at different range sizes were identified using Multi-Site Generalized Dissimilarity Modelling (MS-GDM) of zeta diversity. Bioclimatic factors significantly influenced community turnover in inland areas with large diurnal temperature ranges, and in areas with high precipitation. Communities separated by large geographical distances had significantly different compositions, indicating little contribution of long-range propagule movement by humans, and the presence of localized introduction hubs within the country which harbour unique species compositions. Analyses also showed a significant contribution of road density to turnover, which may be moderated by the habitat service provided by road verges. The same is true for natural dispersal via rivers in arid areas. The distribution of naturalized tree and shrub species is geographically clustered and forms six alien bioregions that are distinct from the South African biomes.